The Role of Innovation and The Entrepreneurship Ecosystem in Creating Sustainable Development of Islamic Endowment (Waqf) : A Systematic Review - Maulina, Rindawati; Dhewanto, Wawan; Faturohman, Taufik (School of Business, IPB University (SB-IPB), 2025)
Background: A more focused examination of the specific themes of waqf, innovation, and entrepreneurship is needed to deepen our understanding of their role in promoting the sustainability of waqf institutions and benefiting the community. Purpose: This study attempts to present literature works over 50 years related to sustainable waqf development from the perspective of innovation and entrepreneurship ecosystem (EE).Design/methodology/approach: This study employed a two-step qualitative methodology. First, a bibliographic analysis was conducted. Second, a content analysis of all reviewed articles was performed.Findings/Result: This study discovered that process and product innovation was the most frequently carried out by previous research. Meanwhile, position and paradigm innovation are still uncommon. The study proposes that the mediating role of EE between innovation and sustainable waqf development, as well as highlighting how factors of sharia compliance, governance, transparency and accountability, community engagement, and stakeholders’ collaboration can moderate this relationship.Conclusion: This study contributes to the literature on waqf and entrepreneurship by providing valuable insights for academics seeking to develop sustainable waqf models and innovations. Practically, this study can inform various stakeholders in formulating strategies to promote sustainable waqf development and contribute to national economic growth.Originality/value (State of the art): To the author's knowledge, previous research has yet to specifically discuss the waqf theme concerning innovation and entrepreneurship ecosystem (EE) in supporting the growth and sustainability of waqf development. Keywords: sustainable development, innovation, entrepreneurship ecosystem, waqf, systematic review